Normed Children Effects of Gender and Sex Related Normativity on Childhood and Adolescence - Schneider, Erik; Baltes-Löhr, Christel (Gender Studies, 2018)
Gender- and sex-related norms have an impact on us from the first to the last day of our lives. What are the effects of such norms on the education of children and adolescents? Conveyed via parents/family, school, and peers, they seem to be an inseparable part of human relations. After its favorable reception in German-speaking countries from 2014 onwards, this title is now available in English. The texts show that the traditional assumption of a dualistic, bipolar normativity of sex and gender leads to children being taught gender-typical behavior. The contributions in this volume explore the reasons for these practices and open the debate on the divergence between the prevailing norms and the plurality of different life plans. In addition, the book helps to disengage the topic of sex and gender from a hitherto narrowly circumscribed context of sexual orientation. The contributions point the way towards a culture of respect and mutual acceptance and show new methodological as well as theoretical approaches, e.g. by introducing the figure of the continuum, so that, in future research projects, more than just the two sexes and genders of female and male might be considered as a new normality.